Implementation of a new program of gestational diabetes screening and management in Morocco: a qualitative exploration of health workers' perceptions - Bettina Utz; Bouchra Assarag; Touria Lekhal; Wim Van Damme; Vincent De Brouwere (BMC, 2020)
Abstract Background Gestational diabetes mellitus (GDM) is associated with an increased risk for a future type 2 diabetes mellitus in women and their children. As linkage between maternal health and non-communicable diseases, antenatal care plays a key role in the primary and secondary prevention of GDM associated adverse outcomes. While implementing a locally adapted GDM screening and management approach through antenatal care services at the primary level of care, we assessed its acceptability by the implementing health care providers. Methods As part of a larger implementation effectiveness study assessing a decentralized gestational diabetes screening and management approach in the prefecture of Marrakech and the rural district of Al Haouz in Morocco, we conducted four focus group discussions with 29 primary health care providers and seven in-depth interviews with national and regional key informants. After transcription of data, we thematically analyzed the data using a combined deductive and inductive approach. Results The intervention of screening and managing women with gestational diabetes added value to existing antenatal care services but presented an additional workload for first line health care providers. An existing lack of knowledge about gestational diabetes in the community and among private health care physicians required of public providers to spend more time on counselling women. Nurses had to adapt recommendations on diet to the socio-economic context of patients. Despite the additional task, especially nurses and midwives felt motivated by their gained capacity to detect and manage gestational diabetes, and to take decisions on treatment and follow-up. Conclusions Detection and initial management of gestational diabetes is an acceptable strategy to extend the antenatal care service offer in Morocco and to facilitate service access for affected pregnant women. Despite its additional workload, gestational diabetes management can contribute to the professional motivation of primary level health care providers. Trial registration clinicaltrials.gov ; NCT02979756.